Analisis peningkatan kinerja pemeliharaan mesin dengan Total Productive Maintenance (TPM) pada mesin boiler pabrik kelapa sawit PT. Perkebunan Nusantara VI unit usaha Rimbo Dua Tebo-Jambi - Firman, Firman; Thabrani, Gesit; Violeta, Vega Pamela (Jurnal Kajian Manajemen Bisnis, 2019)
The implementation of Total productive Maintenance (TPM) is to improve maintenance performance in production machine at PT. Perkebunan Nusantara VI Rimbo Dua. This is a descriptive research. The analysis used overall equipment effectiveness (OEE), OEE six big losses, pareto diagrams and cause and effect diagrams. As a result PTPN VI Rimbo Dua had a problem about machine performance value, it was lower than the world class standard about 71.85% (â‰¤ 95%). Caused of the low OEE value (65,16%) is high idling and minor stoppages and reduced speed losses value. To improve this problem the company is implementing TPM, with planning 8 TPM pillars as the foundation for implementing TPM.Keywords: Total Productive Maintenance, Pareto Diagram, Cause and Effect Diagram